Anti-psoriatic effects of Honokiol through the inhibition of NF-κB and VEGFR-2 in animal model of K14-VEGF transgenic mouse - Jiaolin Wen; Xianhuo Wang; Heying Pei; Caifeng Xie; Neng Qiu; Shucai Li; Wenwen Wang; Xia Cheng; Lijuan Chen (Elsevier, 2015)
Honokiol (HK), a biphenolic neolignan isolated from Magnolia officinalis, has been reported to possess anti-inflammatory and anti-angiogenic activaties. In this study, our aim was to investigate anti-psoriatic activities of HK and the involved mechanisms. In vitro, the effects of HK on the regulation of Th1/Th2 and TNF-α-induced NF-κB (p65) activation were analyzed by respective FCS and immunofluorescence. Additionally, the K14-VEGF transgenic model was used for the in vivo study. ELISA and Q-PCR were performed to evaluate serum levels of Th1/Th2 cytokines and their corresponding mRNA expressions. Effects on VEGFR-2 and p65 activation, as well as other angiogenic and inflammatory parameters were studied by immunostainings. Importantly, we found that HK significantly decreased the ratio of Th1/Th2-expression CD4+ T cells and inhibited TNF-α-induced activation of NF-κB. The morphology and histological features of psoriasis were effectively improved by HK treatment. The expression of TNF-α and IFN-γ, and their corresponding mRNA levels were down-regulated and the expression of nuclear p65, VEGFR-2, as well as related phosphorylated proteins (p-VEGFR-2, p-ERK1/2, p-AKT and p-p38) were also suppressed. Overall, these results in our study suggested that HK exhibits anti-psoriatic effects through the inhibition of NF-κB and VEGFR-2.